2019
DOI: 10.1037/adb0000430
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in marines’ reports of PTSD symptoms and problem alcohol use across the deployment cycle.

Abstract: Posttraumatic stress disorder (PTSD) and alcohol misuse are commonly co-occurring problems in active-duty service members (SMs) and veterans. Unfortunately, relatively little is known about the temporal associations between these problems in the acute period following exposure to combat stressors. Discerning the temporal associations between these problems across the deployment cycle could inform prevention and treatment efforts. In this study, we examined the association between PTSD symptom severity and prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…This suggests that ongoing PTSD rather than combat exposure is the major risk factor for ongoing AUDs. Several explanations have been advanced for the association between PTSD and AUDs (discussed elegantly by Simpson et al, 2014, andBerke et al, 2018). These encompass a "mutual maintenance" model, whereby PTSD symptoms lead to increased alcohol use, which, in turn, exacerbates or maintains PTSD symptoms; a "self-medication" model, whereby alcohol is used to ameliorate the symptoms of PTSD; and a "common factors" model, whereby risk factors for PTSD and AUDs are shared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that ongoing PTSD rather than combat exposure is the major risk factor for ongoing AUDs. Several explanations have been advanced for the association between PTSD and AUDs (discussed elegantly by Simpson et al, 2014, andBerke et al, 2018). These encompass a "mutual maintenance" model, whereby PTSD symptoms lead to increased alcohol use, which, in turn, exacerbates or maintains PTSD symptoms; a "self-medication" model, whereby alcohol is used to ameliorate the symptoms of PTSD; and a "common factors" model, whereby risk factors for PTSD and AUDs are shared.…”
Section: Discussionmentioning
confidence: 99%
“…There is a distinct lack of follow‐up studies, with most reports presenting findings from samples of recent returnees who are often assessed with self‐administered group surveys, giving a short‐term perspective on alcohol use and PTSD. Studies of recent returnees that have commenced before and immediately following deployment (e.g., Berke et al., 2018) do not provide longer‐term information on aging veterans, particularly on cohorts from earlier service eras who did not receive focused early attention to intervention programs. The factors that increase the risks of long‐term AUDs over time (i.e., the perpetuating factors), are unclear; in addition, the role of the DSM‐III and DSM‐IV PTSD symptom clusters of intrusion, numbing and avoidance, and hyperarousal in long‐term alcohol misuse is also in question.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature of 55 studies of PTSD patients found non-response rates as high as 50% and dropout rates ranging widely and depending on the nature of the study population [ 20 ]. In a meta-analysis assessing war trauma [ 21 ], dropout rates ranged from 5% to 78%, and in a recent review of data from three clinical trials of evidence-based PTSD treatments in military service members, the dropout rate was 31% [ 22 ]. These findings suggest new and innovative strategies are needed to improve treatment retention, especially in a new and complex situation such as the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis 26 that assessed dropout rates in war trauma ranged from 5% to 78%, suggesting new and innovative strategies to improve treatment retention. More recently, Berke et al 27 reviewed data from three clinical trials of evidence-based PTSD treatment (namely CPT, present-centered therapy, and PE) in military service members and reported a 31% dropout rate. They suggested that dropout from PTSD treatment is significantly associated with treatment outcome, and that new strategies are needed to reduce dropout rates, especially in group and trauma-focused therapies.…”
Section: Introductionmentioning
confidence: 99%